EFEK ANTIHIPERLIPIDEMI INFUS DAUN SAMBILOTO (Andrograpidis paniculata) PADA HEWAN COBA KELINCI ( Orictolagus cuniculus) DENGAN PARAMETER KOLESTEROL DAN TRIGLISERIDA - Sukmawati Syarif; Aulia Wati; Hendra Herman (As-Syifaa Jurnal Farmasi, 2011)
This research is done to know whether infuse of sambiloto leaf can reduce cholesterol and trigliserida value in the blood or not. For reducing cholesterol and trigliserida value in the blood, we want to know the most effective concentration of infuse of sambiloto leaf ( Andrograpidis paniculata).In this research, the method is used is draw up samples, substancions, experimental animals, treatment with experimental animal and measuring cholesterol and trigliserida value.All sample can reduce cholesterol and trigliserida value at concentration 10%, 15%, or 20%, sample with concentration 15% and 20% reduce cholesterol value is better than sample with concentration 10%. Sample with concentration 15% and 20% have reducing effect of trigliserida value same with simvastatin.Analyze using ANAVA (analys variant) with continuing test using LSD at belief standart 0,05, in conclusion, infuse of Sambiloto leaf can reduce not only cholesterol but also trigliserida value in male rabbits.Key Word : Antihiperlipidemi, Andrograpidis paniculata, cholesterol and trigliserida.